Contrasting Geomorphic and Stratigraphic Responses to Normal Fault Development During Single and Multi-Phase Rifting - Pechlivanidou, Sofia; Geurts, Anneleen H.; Duclaux, Guillaume; Gawthorpe, Robert L.; Pennos, Christos; Finch, Emma (Frontiers in Earth Science, 2022)
Understanding the impact of tectonics on surface processes and the resultant stratigraphic evolution in multi-phase rifts is challenging, as patterns of erosion and deposition related to older phases of extension are overprinted by the subsequent extensional phases. In this study, we use a one-way coupled numerical modelling approach between a tectonic and a surface processes model to investigate topographic evolution, erosion and basin stratigraphy during single and multi-phase rifting. We compare the results from the single and the multi-phase rift experiments for a 5 Myr period during which they experience equal amounts of extension, but with the multi-phase experiment experiencing fault topography inherited from a previous phase of extension. Our results demonstrate a very dynamic evolution of the drainage network that occurs in response to fault growth and linkage and to depocentre overfilling and overspilling. We observe profound differences between topographic and depocenter development during single and multi-phase rifting with implications for sedimentary facies architecture. Our quantitative approach, enables us to better understand the impact of changing extension direction on the distribution of sediment source areas and the syn-rift stratigraphic development through time and space.